TINGKAT PEMAHAMAN TERHADAP SAK ETAP: STUDI EMPIRIS PADA MAHASISWA YANG BERASAL DARI SMK DAN SMA - Fidiana, Fidiana (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2011)
The main objective of the research is to prove level of the understanding toward accounting principle in the SAK Etap of Accounting students of STIESIA Surabaya based on their previous study that is from vocational study or from general study. The Population of the research is the Accounting students of Stiesia who are assigned at semester 3 on academic year of 2011/2012. The instrument of collecting data is questioner, which is used to reveal variable of recognition, measurement and reporting of understanding SAK Etap concept. Each instrument has been tasted and it fulfills the term of validity and reliability. Based on the Levene test toward 86 students with various background studies, there is no different significantly level the understanding of recognition, measurement, and reporting of understanding SAK concept. Keywords: recognition, measurement, reporting, understanding, SAK ETAP